Homelessness in autistic women: Defining the research agenda. (December 2022) - Lockwood Estrin, Georgia; Aseervatham, Victoria; De Barros, Clara M; Chapple, Tara; Churchard, Alasdair; Harper, Monique; Jones, Emily JH; Mandy, William; Milner, Victoria; O'Brien, Sarah; Senju, Atsushi; Smith, Chloe; et al.
Background: Current evidence suggests that autistic individuals are at high risk for becoming and remaining in a cycle of homelessness. Key risk factors for homelessness disproportionately affect autistic people; however, we have limited understanding of how to best support autistic individuals accessing services. This gap in the evidence base is particularly acute for autistic women. Objective: As a first step to address this gap, we aimed to (1) map gaps in knowledge and practice; (2) identify priority areas for research and (3) develop recommendations for how to implement novel research and practice in this area. Methods: We conducted a collaborative workshop with an interdisciplinary group of 26 stakeholders to address our aims. Stakeholders included autistic women with experience of homelessness, researchers, health professionals, NGO representatives, and service providers. Results and recommendations: Two research priority areas were identified to map the prevalence and demographics of autistic women experiencing homelessness, and to delineate risk and protective factors for homelessness. Priority areas for improving provision of support included staff training to improve communication, awareness of autism and building trust with service providers, and recommendations for practical provision of support by services. Conclusions: Future research is critical to increase our knowledge of the pathways leading to homelessness for autistic women, and barriers to engaging with homelessness and social services. We need to use this knowledge to develop new ways of delivering targeted and inclusive support for autistic women, which could prevent or shorten periods of homelessness.